Darwin's finches: Population variation and sympatric speciation - Grant, B. R. (1979)
The classical model of the adaptive radiation of Darwin's finches is one of repeated speciation in allopatry. Evidence presented here suggests that sympatric specification may have contributed to the radiation. On Isla Genovesa Geospiza conirostris displays several features that are consistent with a model of sympatric speciation. Males are polymorphic in song type. Those singing song A have significantly longer bills than those singing song B. The two groups of males forage in different ways that are functionally associated with the bill differences, particularly in the nonbreeding season when food is probably limiting. Territories of mated song A and song B males alternate in space, whereas territories of unmated males do not. This suggests that females can discriminate between males on the basis of song and position, and the pattern is consistent with a hypothesis of assortative mating within song groups. The population is therefore polymorphic; the morphs occupy different niches in which they may be separately regulated and they could be on the way to achieving full reproductive isolation through assortive mating. It is suggested that the population may oscillate between fission and fusion tendencies due to a changing selection regime in this variable and unpredictable environment. There is no evidence that one of the morphs originated allopatrically and then immigrated to Genovesa. The possibility of sympatric speciation being partly responsible for the adaptive radiation, dismissed more than 30 years ago, should be reinstated.